Global development finance ... - World Bank. International Economics Department (Washington, D.C. : International Bank for Reconstruction and Development/The World Bank, 2007)
"Authoritative review of developing countries' external debt and financial flows. Provides consolidated statistics for all developing countries, including those that do not report to the World Bank's Debtor Reporting System (DRS)."
"World Bank software"--Disk label.
"Data on diskette with STARS retrieval system"--Disk label.
"Single-user version"--Disk label.
Numerical data and text.
Also issued in print and CD-ROM formats.
System requirements: IBM PC or compatible with at least 512 K memory, and MS-DOS version 2.1 or higher.
Keywords: Loans, Foreign -- Developing countries -- Statistics -- Databases; Debts, External -- Developing countries -- Statistics -- Databases; International finance -- Statistics -- Databases; Finance -- Developing countries -- Databases; Finance; International finance -- Statistics; Developing countries; Floppy disks; Databases